1981
DOI: 10.1121/1.2018716
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of obstruent voicing in german is incomplete

Abstract: A familiar phonological neutralization rule is the merger of voiced and voiceless obstruents in syllable-final position in German. Thus, the /d/ in Leid ‘sorrow’ is pronounced [-voice] like the /t/ in leit ‘lead.’ A spectrographic test of minimal pairs by nine Germans, however, revealed (1) vowels before underlying voiced consonants were 10% longer than before underlying voiceless ones, (2) there was a slightly longer interval of glottal pulsing into the consonant closure for the underlying voiced consonants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 0 publications
2
64
0
1
Order By: Relevance
“…Roettger et al (2014) make a case for this, looking at near-neutralization of voicing in German. Several studies find small, but systematic differences in ostensibly neutralized word-final stops in German (Port et al, 1981;Port & Crawford, 1989;Charles-Luce, 1985;Kleber et al, 2010). Similar observations concerning near-neutralization have been made for voicing in Catalan (Dinnsen & Charles-Luce, 1984) and Russian (Kharlamov, 2014).…”
Section: Discussionsupporting
confidence: 49%
“…Roettger et al (2014) make a case for this, looking at near-neutralization of voicing in German. Several studies find small, but systematic differences in ostensibly neutralized word-final stops in German (Port et al, 1981;Port & Crawford, 1989;Charles-Luce, 1985;Kleber et al, 2010). Similar observations concerning near-neutralization have been made for voicing in Catalan (Dinnsen & Charles-Luce, 1984) and Russian (Kharlamov, 2014).…”
Section: Discussionsupporting
confidence: 49%
“…At the same time, experimental studies have repeatedly shown that speakers of neutralizing languages maintain acoustic differences between phonologically voiced versus voiceless final obstruents and that listeners can often identify the voicing setting of such segments at an above-chance level (e.g., Port and O'Dell 1985;Warner et al 2004). The current study investigates how such identification responses vary depending on whether the perceptual stimuli were recorded using reading vs. non-reading procedures and with vs. without full minimal pairs in the experimental list.…”
Section: Introductionmentioning
confidence: 99%
“…Incomplete neutralization has also been attested in the domain of perception, where the rates of voiced responses vary depending on the phonological voicing setting of the final consonant despite its phonetic devoicing (Port and O'Dell 1985;Port and Crawford 1989;Slowiaczek and Szymanska 1989;Warner et al 2004;Röttger et al 2011). For example, during forced-choice two-alternative identification tasks, speakers of German have shown above-chance-level performance on voicing, with the majority of phonologically voiced but phonetically devoiced segments being attributed to the voiced category (e.g., Port and O'Dell 1985;Port and Crawford 1989;Röttger et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations